Optical management for back-contact perovskite solar cells with diverse structure designs. (1st April 2022) - Liu, Zunke; Yang, Zhenhai; Yang, Weichuang; Sheng, Jiang; Zeng, Yuheng; Ye, Jichun
Highlights: Three types of IBC structures were conducted for perovskite solar cells by numerical simulations to review their optical response. Anti-reflection coating with an optimal thickness of 70–80 nm plays an important in determining the optical performance. The optimal sizes are confirmed by sweeping the structure parameters, suggesting a high photocurrent density of 24.49 mA/cm 2 . The light-trapping mechanism is revealed by the position-dependent current density and electric-field distributions. Abstract: Interdigitated back-contact (IBC) structure design is a promising alternative to further promote the optical absorption and the power conversion efficiency of perovskite solar cells (PSCs). However, their full potential has not been reached owing to the absence of the advanced structure designs and a lack of a deep understanding on the related physics mechanism. In this paper, we proposed three typical IBC configurations featuring flat perovskite layer, textured electron transport layer (ETL) and hole transport layer (HTL), and textured HTL but flat ETL. By the numerical simulations, the optical properties of the three related designs are investigated systematically. The simulation results reveal that anti-reflection coating (ARC) thickness plays an important in determining the device performance and the optimal ARC thickness is suggested to be 70–80 nm. The optimal structure sizes are confirmed by optimizing the structure parameters. In addition, the light-trapping mechanism is clarified by the position-determined photocurrent density and the spatial electric field distributions. Moreover, dependence of optical response under the various perovskite thickness is checked, suggesting that textured IBC structure design is good to achieve high optical absorption. The simulation results demonstrated in this paper provide a valuable guide to design IBC PSCs with high optical performance.